2011
DOI: 10.1088/0953-8984/23/4/045401
|View full text |Cite
|
Sign up to set email alerts
|

A Raman scattering study of pressure-induced phase transitions in nanocrystalline Bi2MoO6

Abstract: Lattice dynamics calculations and a high-pressure Raman scattering study of nanocrystalline Bi(2)MoO(6), a member of the bismuth-layered Aurivillius family of ferroelectrics, are presented. These studies showed the onset of two reversible second-order or weakly first-order phase transitions near 2.5 and 4.5 GPa as well as some subtle structural changes at 8.2 GPa. Symmetry increases upon application of pressure and the first phase transition involves, most likely, the loss of the MoO(6) tilt mode around a pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…Based upon the equation of state, it was observed that Bi 2 MoO 6 undergoes a phase transformation at $ 6.8 GPa which confirms the previous reports from Raman experiments [14,15]. This high-pressure phase continues to be indexed to an orthorhombic structure and upon decompression from $47 GPa reverts to the low-pressure structure at $1.7 GPa.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Based upon the equation of state, it was observed that Bi 2 MoO 6 undergoes a phase transformation at $ 6.8 GPa which confirms the previous reports from Raman experiments [14,15]. This high-pressure phase continues to be indexed to an orthorhombic structure and upon decompression from $47 GPa reverts to the low-pressure structure at $1.7 GPa.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to this behavior, distortion of the WO 6 octahedra significantly increases in Bi 2 WO 6 with increasing pressure [18]. It was also shown that the high-pressure phases of Bi 2 WO 6 and Bi 2 MoO 6 are orthorhombic and most likely centrosymmetric [14,15,18].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additional weak spin-orbit doublet peaks with binding energy of 157.92 eV for Bi 4f 7/2 and 163.40 eV for Bi 4f 5/2 are also detected, suggesting that some of bismuth exist as the (+3 − ) valence state [16]. Probably, the Bi (+3− ) formal oxidation state could be attributed to the substoichiometric phase within the microsized plates [16] [23][24][25].…”
Section: Resultsmentioning
confidence: 97%